'HOW TO READ A ROMAN PORTRAIT'? OPTATIAN PORFYRY, CONSTANTINE AND THE VVLTVS AVGVSTI. (20th September 2016) - Squire, Michael
Abstract : This article takes its lead from research into the 'language' of Roman portraiture. More specifically, it explores a work that literalizes the idea of 'reading' a Roman portrait (to quote Sheldon Nodelman's classic phrase): a picture-poem by Publilius Optatianus Porfyrius — a much maligned poet active in the first decades of the fourth centuryad — that purports, through its iconotextual form, to visualize the countenance of the emperor Constantine ( uultus Augusti ). After a brief introduction to Optatian and his œuvre, the article offers a close reading of his third poem, demonstrating the sophisticated ways in which it probes the latent iconic potential of written script. What particularly interests me about this case study is its underlying paradox: on the one hand, Optatian boasts that his painted page will outstrip antiquity's most celebrated painter (it 'will dare outdo the waxes of Apelles', uincere Apelleas audebit pagina ceras ); on the other, the actual form of the picture seems to eschew mimetic modes of representation, rendering Constantine's 'portrait' a geometric pattern. So how should we make sense of this image? What does the poem reveal about ideas of portraiture in the fourth century? And how might we contextualize Optatian's abiding fascination with the limits of 'seeing' and 'reading'? Abstract : Questo articolo prende le mosse dalle ricerche sul 'linguaggio' del ritratto romano. Più nel dettaglio, analizza un'opera che prende alla lettera l'idea di 'leggere' un ritratto romano (per citare la classica frase di Sheldon Nodelman): un carme figurato di Publilius Optatianus Porfyrius, poeta su cui molto si è malignato, attivo nei primi decenni del quarto secolo d.C. Il carme afferma, attraverso la sua forma icono-testuale, di visualizzare l'espressione del viso dell'imperatore Costantino ( uultus Augusti ). Dopo una breve introduzione a Optaziano e alla sua opera, l'articolo offre una lettura serrata del terzo carme, dimostrando i modi sofisticati con i quali indaga il latente potenziale iconico della parola scritta. Ciò che interessa particolarmente in questo caso è il paradosso sotteso: da un lato, Optaziano si vanta che la sua 'pagina dipinta' supererà il pittore più celebre dell'antichità (oserà sorpassare le cere di Apelle, uincere Apelleas audebit pagina ceras ); dall'altro, la forma reale dell'immagine sembra rifuggire modi mimetici di rappresentazione, rendendo il 'ritratto' di Costantino con un motivo geometrico. Come è possibile dare un senso a questa immagine? Che cosa rivela il poema sull'uso del ritratto del IV secolo? E come potremmo contestualizzare la profonda fascinazione di Optaziano per i limiti del 'vedere' e del 'leggere'?